2002
DOI: 10.1086/340413
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD4 and CCR5 Expression and Human Immunodeficiency Virus Type 1 Entry in CD40 Ligand–Stimulated Macrophages

Abstract: The effects of a soluble trimeric CD40 ligand (CD40L) agonist on the expression of CD4 and CCR5 and on human immunodeficiency virus (HIV) type 1 entry into and replication in human macrophages were investigated. CD40L increased the number of CD4 and CCR5 antibody-binding sites and the percentage of CD4- and CCR5-expressing cells. Infection of CD40L-stimulated macrophages with HIV-1 resulted in a marked increase of viral DNA with respect to controls, as demonstrated by polymerase chain reaction assay. HIV-1 p24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 50 publications
(59 reference statements)
0
8
0
1
Order By: Relevance
“…The CD40L-induced secretion of -chemokines is mediated by the rapid activation of MAPK signalling pathways (Bakri et al, 2002;Cotter et al, 2001;di Marzio et al, 2000;Kornbluth et al, 1998). When monocytes differentiate in the presence of CD40L an opposite effect is described, leading to the up-regulation of CD4 and CCR5 and to an increase in HIV-1 entry, but not to an increase in total virus production (Bergamini et al, 2002). Thus, CD40L activation of macrophages may lead to different and even opposite outcomes depending on the viral tropism and the cellular environment.…”
Section: Macrophage-t Cell Interplay and Hiv-1 Activationmentioning
confidence: 99%
“…The CD40L-induced secretion of -chemokines is mediated by the rapid activation of MAPK signalling pathways (Bakri et al, 2002;Cotter et al, 2001;di Marzio et al, 2000;Kornbluth et al, 1998). When monocytes differentiate in the presence of CD40L an opposite effect is described, leading to the up-regulation of CD4 and CCR5 and to an increase in HIV-1 entry, but not to an increase in total virus production (Bergamini et al, 2002). Thus, CD40L activation of macrophages may lead to different and even opposite outcomes depending on the viral tropism and the cellular environment.…”
Section: Macrophage-t Cell Interplay and Hiv-1 Activationmentioning
confidence: 99%
“…It has been demonstrated that trimeric recombinant CD40L can reactivate latent HIV-1 infection in macrophages (Kutsch et al, 2003) as well as stimulate significant viral replication in monocytes-derived macrophages (Bakri et al, 2002). Viral DNA production is increased from HIV-1-infected macrophages stimulated with CD40L (Bergamini et al, 2002). It has also been demonstrated that CD40L treatment of choroid plexus macrophages results in a significant increase in their proliferation (Bragg et al, 2002).…”
Section: Cd40-cd40l Interaction In Microgliamentioning
confidence: 99%
“…Several investigators have reported that activation of macrophages or dendritic cells (DCs) with trimeric CD154 resulted in release of ␤-chemokines and TNF-␣, reduction of cell surface expression of CD4 and CCR5, and resistance to HIV and SIV infection (12,14,30,32,34,35). However, other authors reported either completely opposite results (6) or that this CD154-mediated macrophage activation rendered these cells highly susceptible to infection with CXCR4-dependent viruses (3). Similarly, increased levels of HIV infection have been reported after CD154-mediated activation of Langerhans cell-like DCs (25) and plasmacytoid DCs (15).…”
Section: Discussionmentioning
confidence: 98%
“…Virus levels were calculated according to the method of Reed and Muench (38) and expressed as TCID 50 /10 6 cells. Virus isolation was performed by cocultivation of 10 6 PBMCs with 10 5 CEM-x-174 cells. Virus production, length of cultivation, and criterion for positivity were determined as described above for cell-associated viral loads.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation